Adaptive optics for phase and polarization control - Dai, Y (2019)
Adaptive optics (AO) is a powerful tool for microscopy. It helps to improve the image quality and resolution by correcting the aberrations that arise in the optical system or through external disturbance. Most AO technologies concern phase distortion, which is the main issue in the mainstream microscopies.